1999
DOI: 10.1002/(sici)1097-4628(19990919)73:12<2303::aid-app1>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective promotion of tetrahydrofuran polymerization initiated with heteropolyacid

Abstract: Tetrahydrofuran was polymerized using the heteropolyacid H 3 PW 12 O 40 as the initiator and ethylene oxide as the promoter, which effectively increased the rate and conversion of the polymerization. Water and butylene glycol were used to control the molecular weight of the product in the range of 1000 -3000. The polymer was found to be polyether glycol containing 10 -22 mol % oxyethylene moieties with hydroxyl groups at both chain ends. The melting point was ϳ 10°C lower compared to polytetramethylene ether g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…The peaks of EO moieties in Figure 1 were assigned as we reported in a previous paper [16] and the peaks of TMP moieties were assigned by using the spindecoupling technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks of EO moieties in Figure 1 were assigned as we reported in a previous paper [16] and the peaks of TMP moieties were assigned by using the spindecoupling technique.…”
Section: Resultsmentioning
confidence: 99%
“…In previous paper [16] we reported that the polymerization of THF initiated by PW 12 in low concentration at 0 8C did not proceed or proceeded very slowly. The reaction started normally upon addition of EO, and the propagating chains started with oxyethylene hydroxyl groups (HOCH 2-CH 2 O1) as shown by reaction 1 in Scheme 1.…”
Section: Preparation Of Polyether Triols Using Eo As Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…Heteropolyacids have many applications in science researches [4][5][6][7] and industrial production [8], and it could also replace HF, H 2 SO 4 , and other traditional inorganic corrosive acids in the synthesis of polytetrahydrofuran in mild conditions [9,10]. Because of low specific area (\10 m 2 /g) and dissolution in polar solution, heteropolyacid is not easy to separate from the reaction mixture and its catalytic reaction stability is poor [11].…”
Section: Introductionmentioning
confidence: 99%
“…In these reactions, the aimed catalysts acted as polymerization initiators, and the reaction mechanism was accepted commonly as cationic polymerization [13][14][15][16][17][18][19]. Burrington et al [20] have published on the use of a heteropolyacid salt as catalyst for the cationic polymerization of isobutylene.…”
mentioning
confidence: 99%